Measuring Self-Reported Physical Function in Individuals With TBI: Development of the TBI-QOL Mobility and Upper Extremity Item Banks and Short Forms. Issue 5 (September 2019) - Capó-Lugo, Carmen E.; Kisala, Pamela A.; Boulton, Aaron J.; Choi, Seung W.; Heinemann, Allen W.; Tulsky, David S.
Abstract : Objectives: To describe the development and field testing of the patient-reported outcome measures of Mobility and Upper Extremity function from the Traumatic Brain Injury Quality of Life (TBI-QOL) measurement system, and to evaluate the use of computer adaptive testing. Setting: Five rehabilitation facilities funded as part of the TBI Model Systems network. Participants: Individuals with complicated mild, moderate, or severe traumatic brain injury ( n = 590). Interventions: Not available. Outcome Measures: TBI-QOL Mobility and Upper Extremity item banks. Results: Item response theory and factor analyses supported the unidimensionality of the Mobility and Upper Extremity banks. Descriptive statistics showed a ceiling effect for both measures. Simulated computer adaptive tests (CATs) showed that measurement precision was maintained across administration formats for both measures. The Upper Extremity CAT showed a loss of precision for individuals without impairment and that a higher number of items were required to achieve sufficiently precise measurement, compared to the Mobility CAT. Conclusions: The TBI-QOL Upper Extremity and Mobility item banks achieved good breadth of coverage, particularly among those individuals who have experienced some degree of functional limitation. The use of CAT administration minimizes respondent burden, while allowing for the comprehensive assessment of adults with TBI. The combined use of the TBI-QOL with performance-based measures could guide the development of targeted rehabilitation treatments.